Pengaruh Penggunaan Alat Peraga Batang Napier Terhadap Prestasi Belajar Matematika Siswa Kelas 4 SD Negeri 2 Bataraguru - Rismayani Armin; Novi Lufianti La Ulu (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2022)
The formulation of the problem in this study, Is there a positive and significant effect on the use of the Napier rod props on the mathematics learning achievement of 4th grade students of SD Negeri 2 Bataraguru? The purpose of this study was to determine the effect of using Napier rods teaching aids on student achievement at SD Negeri 2 Bataraguru. This research is a quantitative study using a quasi-experimental method. The research data were analyzed using the average difference test, but previously a descriptive analysis of inferential analysis was carried out which consisted of a prerequisite test, namely the normality test and the homogeneity test. Based on the results of the descriptive analysis, the test score for the experimental class was 76.50, and the average test score was 52.00 for the control class and based on the results of inferential analysis by looking at the normality test, the significant value of the test results in the experimental class was 0.134 and the significant value of the class test. control is 0.200, while the homogeneity test in both classes of student test results shows a significant value of 0.786> 0.005, so it can be said that the two classes are homogeneous. By using the t-test, the significant value is 0.000 <0.05, which means that H0 is rejected. So it can be concluded that there is a positive and significant effect on the use of Napier rods teaching aids on mathematics learning achievement of 4th grade students of SD Negeri 2 Bataraguru.